2016
DOI: 10.4236/health.2016.810104
|View full text |Cite
|
Sign up to set email alerts
|

Ranking of E-Health Barriers Faced by Saudi Arabian Citizens, Healthcare Professionals and IT Specialists in Saudi Arabia

Abstract: Many boundaries are hindering successful utilisation of e-health in the Kingdom of Saudi Arabia (KSA). We have previously proposed an integrated framework of knowledge management and knowledge discovery to overcome barriers of e-health in KSA. Our proposed framework facilitates diabetes self-management for diabetic citizens in the Kingdom. In this paper, we will investigate and rank the barriers of e-health in KSA from the prospective of three stakeholders. We designed a questionnaire which constituted of item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 6 publications
2
22
1
Order By: Relevance
“…Keeping these challenges in mind, the Saudi government is keen to invest in different ICT-based e-health services. 18 Recent studies showed that despite huge spending on various tools like Electronic Medical Coverage (EMC), Electronic Medical Record (EMR), Electronic Health Record (EHR), Picture Archiving and Communication Systems (PACS), the government still face barriers in the adoption of the e-health systems. 1 , 19 These barriers include cultural norms, illiteracy, inadequate knowledge of computer, and other IT skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping these challenges in mind, the Saudi government is keen to invest in different ICT-based e-health services. 18 Recent studies showed that despite huge spending on various tools like Electronic Medical Coverage (EMC), Electronic Medical Record (EMR), Electronic Health Record (EHR), Picture Archiving and Communication Systems (PACS), the government still face barriers in the adoption of the e-health systems. 1 , 19 These barriers include cultural norms, illiteracy, inadequate knowledge of computer, and other IT skills.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 19 These barriers include cultural norms, illiteracy, inadequate knowledge of computer, and other IT skills. 18 …”
Section: Introductionmentioning
confidence: 99%
“…The HIS is information design and build applied to the field of health care, essentially "the management and utilization of patient health care information" (2). Electronic health systems are being used by health professionals to implement daily care management, avoid complications, prevent medical and medication errors, and carry out clinical research (3,4). Electronic health systems make the management of patient records easier and safer while HI supports health professionals, consumers, patients and other stakeholders in their decision-making to achieve desired outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The e-health issues are discussed in details in [62], eliciting several e-health issues to the majority of Information and Communication Technologies (ICTs) being adopted in healthcare in KSA. In this paper, the second issue is discussed.…”
Section: The First Layer: Issues and Complicationsmentioning
confidence: 99%
“…This portal captures valuable guidelines, strategies and best practices that can help diabetic citizens to control their disease. The portal is named Diabetes Self-Management in the Kingdom of Saudi Arabia (DSMKSA) and is designed with respect to barriers affecting ehealth initiatives in KSA as discussed in [62] (see Figure 5).…”
Section: Web Tools For the Seci Modelmentioning
confidence: 99%